Under another sky : journeys in Roman Britain - Higgins, Charlotte, 1972- (The Overlook Press, 2015)
"What does Roman Britain mean to us now? How were its physical remains rediscovered and made sense of? How has it been reimagined, in story and song and verse? Sometimes on foot, sometimes in a magnificent, if not entirely reliable, VW camper van, Charlotte Higgins sets out to explore the ancient monuments of Roman Britain. She explores the land that was once Rome's northernmost territory and how it has changed since the years after the empire fell. Under Another Sky invites us to see the British landscape, and British history, in an entirely fresh way: as indelibly marked by how the Romans first imagined and wrote, these strange and exotic islands, perched on the edge of the known world, into existence"--